Microstructural Features and Hardness Evolution in As-Cast Al–Zn–Mg Alloys Prepared Via Vacuum Arc Melting - Muhammad Ilham Maulana (JST (Jurnal Sains dan Teknologi), 2026)
The relatively low mechanical strength of pure aluminum limits its use as a structural material. Efforts to improve these properties through the addition of alloying elements still require a deeper understanding, particularly regarding the role of Mg on microstructure and hardness. This study aims to analyze the composition of an Al99-x-Zn alloy with optimal Mg variations to improve mechanical properties. This type of research is a laboratory experiment with a comparative design based on composition variations. The research subjects were Al99-x-Zn-Mgx alloys with several variations in Mg content (four different compositions) prepared by vacuum arc melting. Data were collected using microstructural observations (optical microscope) and Vickers hardness test (microhardness tester) as the main instruments. Data analysis was carried out descriptively and quantitatively by comparing grain size and hardness values between composition variations. The results showed that increasing Mg content resulted in a finer and more homogeneous grain structure, and increased hardness to 27.7 HVN, or an increase of 29.8% compared to aluminum without Mg. This finding is consistent with the strengthening mechanism based on the Hall–Petch relationship. The conclusion of this study shows that the addition of Mg is effective in improving the mechanical properties of aluminum through grain refinement. The implication is that Al-Zn-Mg alloys have the potential to be further developed as superior materials for structural and functional applications in the automotive, construction, and biomedical fields.